Pakistan Army Doctrine 2011 : Comprehensive Responce - Pakistan Army (GHQ, Rawalpindi Pakistan Army, 2011)
Content of the book are the writer' personal views and are not to be taken as official opinion/policy
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals